An exploratory study of freestyle footballers in Singapore - Nur Syahirah Rostam (2017)
Freestyle football is the sport plus art of using any part of the body with a soccer ball to surpass rivals in competitions or impress audiences (Freestyle Football Federation, 2016). In Singapore, only two freestyle footballers- Daryl Low and Azri Majilan - had represented Singapore in the international level competition called the Red Bull Street Style (Red Bull Singapore, 2015). The purpose of this study is to clarify the experiences of football freestylers in Singapore (introduced to the researcher by Su Xiuwen Valerie) performing in events, participating in competitions and coaching freestyle football. Exploratory design was chosen as the type of research is social, behavioural and educational sciences. All 6 interviews were individually done separately at their preferred venues. Bracketing was used to reduce the possible harmful outcomes of preconceptions (Tufford & Newman, 2010). Transcripts of the voice recorded interviews were analyzed for key issues, similar opinions and recurring themes. Thematic analysis was employed to examine, arrange and describe themes/patterns in details from the data (Braun & Clarke, 2006). All six participants conveyed positivity as they would continue to perform freestyle football in Singapore despite the sport not being appreciated by many in Singapore. They also have a common value of passion to compete overseas and put Singapore in the limelight. Moreover, they are persistent to spread freestyle football via coaching. Overall, their perseverance through their experiences can help them develop freestyle football in Singapore and inspire others by their core values/beliefs. Keywords: freestyle football, football freestyle, perform, compete, coach